G358 The performance of the new SLICC criteria for the classification of SLE in children. (7th April 2014) - Marks, SD; Sag, E; Ravelli, A; Batu, ED; Tartaglione, A; Khalil, SMA; Ozen, S
Abstract : Aims: The Systemic Lupus International Collaborating Clinics (SLICC) have recently suggested a new set of criteria for the classification of SLE. We aimed to compare the sensitivity and specificities of the ACR criteria and the new SLICC criteria among paediatric SLE patients. Methods: Three main lupus centres from Europe were included in this study. One of these centres was mainly a nephrology centre from UK whereas one was a paediatric rheumatology centre and another combined centre from Europe. Features present at onset in juvenile-onset SLE (jSLE) patients, diagnosed and followed by these three departments between January 2000 to December 2012 were retrospectively analysed. For the specificity analysis, patients admitted to the respective departments in whom ANA was deemed necessary by the caring physician in the diagnostic work-up were included as controls. Results: Both criteria were analysed in 154 jSLE patients with a mean age at disease onset of 12.7 years and 95 controls with a mean age of 8.6 years. In the overall group, the sensitivity and specificity of the ACR criteria were 77% and 92% respectively and that of the SLICC criteria were 99% and 82% respectively. Four haemolytic uraemic syndrome (HUS) patients and four juvenile dermatomyositis (JDM) patients met the SLICC criteria whereas 22 lupus nephritis fell to meet the ACR criteria. Between the three centres there were marked differences among certain clinical features. Renal involvement, neurologic findings, haemolytic anaemia, positive ANA titres and anti-dsDNA were more frequent among children whereas chronic skin lesions were less compared with the reported prevalances of the criteria in adults (p <0.005). Conclusion: In this paediatric cohort, SLICC criteria performed better, was more sensitive (p < 0.001), had fewer misclassifications, but was less specific (p = 0.02). The specificity of the SLICC criteria was reduced with the HUS and JDM cases. The prevalance of certain criteria were significantly different between adults and children, which may necessitate further revision in paediatrics.